1959
DOI: 10.1063/1.1734985
|View full text |Cite
|
Sign up to set email alerts
|

Spherulitic Crystallization in Polypropylene

Abstract: A survey has been made of spherulites formed by the isothermal crystallization of polypropylene from the melt in the temperature range 110°-148°C. Four types of spherulite have been distinguished and their structural morphology, optical properties, melting behavior, and growth rates have been examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
316
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 664 publications
(332 citation statements)
references
References 3 publications
16
316
0
Order By: Relevance
“…The WAXS patterns are presented in Figure 3. Three pronounced diffraction peaks can be observed in Figure 3 at 14, 16,5 and 18,3 ° refer to the α(110), α(040) and α(130) respectively [22][23][24]. No pronounced peak at 20 ° indicating the presence of γ-phase can be observed, thus both the melting curves and WAXS measurements prove that all samples crystallize in the traditional α-modification and neither polymorphic transition nor melting memory effect need to be considered during the experiments [25].…”
Section: Melting and Crystallization Characteristics Of The Studied Smentioning
confidence: 98%
“…The WAXS patterns are presented in Figure 3. Three pronounced diffraction peaks can be observed in Figure 3 at 14, 16,5 and 18,3 ° refer to the α(110), α(040) and α(130) respectively [22][23][24]. No pronounced peak at 20 ° indicating the presence of γ-phase can be observed, thus both the melting curves and WAXS measurements prove that all samples crystallize in the traditional α-modification and neither polymorphic transition nor melting memory effect need to be considered during the experiments [25].…”
Section: Melting and Crystallization Characteristics Of The Studied Smentioning
confidence: 98%
“…Semicrystalline iPP is a polymorphic material, with several crystalline modifications including the monoclinic (α), the trigonal (β), and the orthorhombic (γ) forms [1][2][3][4]. iPP crystallizes essentially into α-modification under traditional processing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…iPP crystallizes essentially into α-modification under traditional processing conditions. The α-form is the thermodynamically stable form according to the literature [1,3,4]. The modification of the crystalline structure of iPP by introduction of nucleating agents is one of the keys of its wide scale application fields.…”
Section: Introductionmentioning
confidence: 99%
“…From several literature reports on morphology of melt-crystallized iPP, it was clearly stated that the crystalline morphology of iPP is dominated by a highly characteristic lamellar branching (crosshatching), with radial and tangential lamellae (chains perpendicular, and parallel to spherulitic radius, respectively) [31,32]. for α-crystalline form [33] The ratio between the number of radial and tangential lamellae determines the sign of birefringence.…”
Section: Morphological Scales In Ippmentioning
confidence: 99%
“…Increasing the temperature of crystallization leads to a reduction in the proportion of tangential lamellae and simultaneously, to a transformation of the birefringence from positive to negative. Transition between negative and positive birefringence occurs when approximately onethird of lamellae are tangential [31,32]. No tangential fibrils form above 155 o C. It was also revealed that the thickness of tangential fibrils was lower than that of radial ones.…”
Section: Morphological Scales In Ippmentioning
confidence: 99%